Multidimensional perspective of Malaysia-Arab relations - Asmady Idris; Remali Yusoff (UTM Press, 2016)
Malaysia has steady relations with most of the Middle Eastern nations including the Islamic Republic of Iran. Although in the early years of post-World War II, particularly during 1957-1952, Malaysia's relations with these nations were only confined to two states, the Kingdom of Saudi Arabia and Egypt.